2019
DOI: 10.1007/s10803-019-04049-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of What Barriers and Facilitators Prevent and Enable Physical Healthcare Services Access for Autistic Adults

Abstract: Autistic people are more likely to: be diagnosed with a range of physical health conditions (i.e. cardio-vascular disease); experience premature mortality (for most disease categories); and experience barriers to effectively accessing healthcare. This systematic review sought to identify studies that report on barriers and facilitators to physical healthcare access for autistic people. A total of 3111 records were screened and six studies were included: two quantitative, two qualitative, and two mixed-methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
195
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(222 citation statements)
references
References 47 publications
16
195
1
1
Order By: Relevance
“…It is suggested that the constant demands of 'fitting-in" to a non-autism world; the stress of "camouflaging" to avoid being perceived as different [60] and the absence of appropriately structured support or daily activities all contribute to high levels of stress, anxiety, and depression. Physical problems and chronic health disorders are also more common than in the general population [74,75] and recent studies highlight the risk of premature mortality [76][77][78]. Premature mortality is particularly high in autistic adults with intellectual disability and epilepsy.…”
Section: Prognosis In Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the constant demands of 'fitting-in" to a non-autism world; the stress of "camouflaging" to avoid being perceived as different [60] and the absence of appropriately structured support or daily activities all contribute to high levels of stress, anxiety, and depression. Physical problems and chronic health disorders are also more common than in the general population [74,75] and recent studies highlight the risk of premature mortality [76][77][78]. Premature mortality is particularly high in autistic adults with intellectual disability and epilepsy.…”
Section: Prognosis In Autismmentioning
confidence: 99%
“…However, due to symptom overlap, diagnostic overshadowing and atypical symptom presentation, assessment, diagnosis, and treatment of co-occurring conditions in autism are complex and challenging [55]. Although individuals with autism should be provided with appropriate medical treatments for all co-occurring medical conditions, it is increasingly apparent that many experience significant difficulties in accessing medical care [77,148]. To promote better physical and mental health and reduce the risk of premature death, systems of care must recognise and adapt to the needs of autistic people, as should be done with any vulnerable group in society.…”
Section: Treatments For Co-occurring Conditionsmentioning
confidence: 99%
“…Our participatory approach and collaboration processes are described in detail elsewhere. Nicolaidis et al, 2019;Nicolaidis et al, 2011;Nicolaidis et al, 2020; Setting, Participants, and Recruitment…”
Section: Academic Community Partnershipmentioning
confidence: 99%
“…These barriers include: communication difficulties, which can lead to misunderstandings by healthcare providers and reduced involvement of patients in healthcare decision making; sensory sensitivities (e.g. around physical examinations); difficulties identifying and/ or describing pains and symptoms and inconsistent specialist clinician training, awareness and knowledge about autism and ID (13)(14)(15)(16). Health providers may also misattribute COVID-19 symptoms to existing medical, mental health or behavioural problems ('diagnostic overshadowing'), increasing risk for severe disease due to missed or late diagnosis (17).…”
Section: Introductionmentioning
confidence: 99%